(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Plasma d-dimer is raised during acute stage of aneurysmal subarachnoid hemorrhage and may be related to outcome. Objective: The aim of the study was to evaluate the association of d-dimer with short term outcome in aneurysmal subarachnoid hemorrhage. Methods: This prospective cohort study was conducted at the department of Neurology, National Institute of Neurosciences & Hospital, for one and half year of period. A total of 120 admitted aSAH patients were enrolled in this study, among them 60 patients had raised d-dimer and another 60 patients had normal d-dimer. D-dimer was measured quantitatively by nephelometric assay using AGAPPE (MISPA-i2) reagent. A value < 0.5mg/L was labelled as normal and e”0.5mg/L was labelled as raised according to user manual. A detailed history and thorough clinical examination were carried out in each patient during admission and follow ups were done during hospital stay to see the complications. Functional outcome was measured at 90 days using Modified Rankin Scale (mRS). A mRS score 0-2 and 3-6 was considered as favorable and unfavorable outcome respectively. Results: Participants with raised d-dimer on admission had significantly higher age, clinical severity (according to World Federation of Neurosurgical Societies Grade, Hunt & Hess grade), high grade hemorrhage in Modified Fisher grade and neurological complications in comparison to those with normal d-dimer (P<0.05). Patients with unfavorable outcome were more in raised d-dimer group than normal ddimer group (76.5% vs 23.5%) (P<0.001). Multivariant logistic regression shows d-dimer is an independent predictor for unfavorable outcome (OR 1.79 [95% CI 1.08-2.36], P=0.018) at 90 days. Conclusion: Raised d-dimer level on admission was significantly associated with unfavourable short-term outcome in aneurysmal SAH patients at 90 days and had an additive predictive value. However, further larger study is recommended